2014
DOI: 10.2478/amm-2014-0228
|View full text |Cite
|
Sign up to set email alerts
|

New Features of Entall Database: Comparison of Experimental and Model Formation Enthalpies/ Nowe Funkcje Bazy Danych Entall: Porównanie Doświadczalnych I Modelowych Entalpii Tworzenia

Abstract: This paper presents a new version of the Entall database of the thermodynamic properties of metals and their alloys. The changes are related to the thermodynamic data of new binary and ternary systems as well as the integration of the database with an application for the modeling of the formation enthalpies of intermetallic phases with the use of the Miedema model. Using this tool, calculations of the enthalpies of formation of 38 intermetallic phases from 12 binary systems were performed and a comparative ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(32 citation statements)
references
References 3 publications
1
30
0
Order By: Relevance
“…The correlation analysis of the formation enthalpy data for the Ga-Li intermetallic phases showed that those calculated by the Miedema model [15,17] are much more exothermic than calculated data (presented by Yuan et al [12] and DFT calculations) as well as the ones from this study. Taking into consideration the experimental problems indicated in this studies and the fact that the results of Yuan et al [12] are one of the possible propositions of optimization, the last three sets of data could be thought of as comparable at this stage of investigations.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…The correlation analysis of the formation enthalpy data for the Ga-Li intermetallic phases showed that those calculated by the Miedema model [15,17] are much more exothermic than calculated data (presented by Yuan et al [12] and DFT calculations) as well as the ones from this study. Taking into consideration the experimental problems indicated in this studies and the fact that the results of Yuan et al [12] are one of the possible propositions of optimization, the last three sets of data could be thought of as comparable at this stage of investigations.…”
Section: Resultsmentioning
confidence: 70%
“…The obtained experimental data of the formation enthalpy of the alloys whose concentrations correspond to the Ga-Li intermetallic phases are shown in Table 2, together with the data calculated by Yuan et al [12], the data calculated by the Miedema model, which were obtained with the use of the Entall Miedema calculator [17] and DFT calculations [18]. Because, the obtained results of formation enthalpy for temperature range of 463-891 K do not vary significantly with the enthalpy of formation data calculated for 298 K, it may indicate lack of the temperature dependence of formation enthalpy of Ga-Li intermetallic phases.…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 shows the binary enthalpy of mixing values based on Miedema semi-empirical model. In addition, the enthalpy of formation for Cu-Cr with atomic ration 1:1 is 18.530117 kJ mol −1 , ΔH (Cu in Cr) is 49.286705 kJ mol −1 , and ΔH (Cr in Cu) is 49.793041 kJ mol −1 [29]. As a result of positive enthalpy of mixing, segregation phenomenon will be promoted leading to the formation of ID rich in Cr and Fe.…”
Section: Edx Analysismentioning
confidence: 99%
“…By applying the same reasoning to the case of Pd-capped thin films of pure magnesium [9], in which Mg and Pd form an alloy only at a very thin (less than 2 nm thick) Mg=Pd interface, it is clear that the alloying model of Chung et al [10] cannot explain the observed large increases of hydrogen loading pressure for films as thick as 40 nm. Furthermore, as Mg and Ni have an enthalpy of mixing (H mix MgNi ¼ −5.6 kJ=mol) that is an order of magnitude smaller than the one of Mg with Pd (H mix MgPd ¼ −43 kJ=mol) [30,31], the model of Chung et al would predict large differences for the loading pressures of Ni-and Pd-capped Mg films. This prediction is contrary to what we observed experimentally [9].…”
mentioning
confidence: 99%